2022
DOI: 10.3389/fpsyg.2022.910598
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ambiguity Tolerance and Enthusiasm on Chinese University Teachers’ Burnout

Abstract: Educators face numerous vague conditions in their daily practice and they must manage students with diverse characters that lead to burnout. In addition, tolerance of ambiguity is a term used by educators as the capability to control new, complicated or insoluble situations. Moreover, educator enthusiasm and its effect on instruction was neglected. And due to the essential function that teachers’ burnout plays in the efficiency of their achievement in the scholastic cycle, the present study inspected whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Likewise, in the research conducted by Yang and Xie (2022) , which examined 495 Chinese university professors, both men and women, the results revealed that teacher burnout is influenced by Ambiguity Tolerance and enthusiasm. Furthermore, a constructive relationship was found between Tolerance for Ambiguity and enthusiasm, both predictors of teacher burnout (Higher Ambiguity Tolerance and enthusiasm lead to lower burnout).…”
Section: Introductionmentioning
confidence: 96%
“…Likewise, in the research conducted by Yang and Xie (2022) , which examined 495 Chinese university professors, both men and women, the results revealed that teacher burnout is influenced by Ambiguity Tolerance and enthusiasm. Furthermore, a constructive relationship was found between Tolerance for Ambiguity and enthusiasm, both predictors of teacher burnout (Higher Ambiguity Tolerance and enthusiasm lead to lower burnout).…”
Section: Introductionmentioning
confidence: 96%